Computer based quantitative analysis of capillary abnormalities in systemic sclerosis and its relation to plasma concentration of von Willebrand factor. Issue 1 (January 1996) - Scheja, A; Akesson, A; Niewierowicz, I; Wallin, L; Wildt, M; Wollheim, F A
Abstract : OBJECTIVES--To evaluate an objective and quantitative method for assessment of capillary abnormalities in systemic sclerosis (SSc). METHODS--Nailfold capillaries were investigated by capillary microscopy and photographed in 17 consecutive SSc patients (five with diffuse cutaneous systemic sclerosis (dSSc) and 12 with limited cutaneous systemic sclerosis (lSSc)) and in 17 healthy controls. Investigators having no access to clinical data made drawings from magnified projections of coded photographs and analysed them using a computer program. Capillary density (capillary loops/mm in the distal row) and median capillary loop area were calculated. Presence of functional or organic arterial changes was evaluated by measurement of finger pressure with finger cooling. Plasma concentration of von Willebrand factor (VWF) was analysed using an enzyme linked immunosorbent assay (ELISA). RESULTS--In 16 of 17 SSc patients and 13 of 17 controls the technical quality of the photographs was sufficient for computer analysis. Capillary density was decreased in dSSc (median 6.9 loops/mm) and in lSSc (median 3.8 loops/mm) compared with healthy controls (8.9 loops/mm) and median capillary loop area was increased in dSSc (7.3 x 10(-3) mm2) and in lSSc (8.5 x 10(-3) mm2) compared with healthy controls (5.0 x 10(-3) mm2). An inverse relation was found between capillary density and median capillary loop area in SSc patients. Plasma VWF was increased in patients (median 401 IE/l in dSSc and 409 IE/l in lSSc) compared with controls matched for age and sex (median 276 IE/l). Computer based analysis showed capillary density below the control range and median capillary loop area above the control range in 14 of 16 SSc patients. Measurement of finger pressure with finger cooling showed organic vascular changes in nine of 13 SSc patients. CONCLUSION--Computer based quantitative analysis has low interobserver variability and is a quantitative and sensitive method of assessing capillary abnormalities in SSc.